KOMUNIKASI INTERPERSONAL DALAM SINETRON (Tinjauan Mengenai Romantic Relationship dalam Sinetron Si Doel Anak Sekolahan) - Yuliarti, Monika Sri (KOMUNITAS)
Soap opera is one of the the most popular products of mass media (television). âSi Doel Anak SekolahanâÂ isÂ oneÂ ofÂ theÂ mostÂ famousÂ IndonesiaÂ soap opera.Â Meanwhile,Â oneÂ ofÂ theÂ mass mediaÂ functionÂ isÂ socialization/Â transmissionÂ ofÂ socialÂ valuesÂ function,Â inÂ whichÂ theÂ mass media display the values held by certain people inÂ itâs program, which later, audiences will adopt them into their daily lives. Romantic relationship is one the relationship that is created from the process of interpersonal communication between people. On the other hand, soap opera consists of many values of the romantic relationship. This study findings are: there are 4Â valuesÂ ofÂ romanticÂ relationshipÂ whichÂ isÂ shownÂ in thisÂ soapÂ opera,Â whichÂ isÂ love, commitment, passion constructive, and intimacy. Those values tend to embodied in non verbal language,Â andÂ theÂ trendÂ isÂ stillÂ withinÂ inÂ theÂ limitsÂ basedÂ onÂ eastÂ cultureÂ ofÂ Indonesia. Meanwhile, from three main characters involved in alove triangle story, a character who is described tends to apply romantic relationship values is Zaenab. Keywords: romantic relationship, si Doel, sinetron,interpersonal communication